GENDERED SPACE TRANSGRESSORS: STUDY OF TWO YORUBA FEMALE DÙNDÚN DRUMMERS - Samuel, Kayode (International Library of African Music, 2018)
The contemporary Nigerian musical landscape occasionally becomes a site for contesting and negotiating the established ideology of Yoruba patriarchy. These movements are evident in many women's decisions to venture into drumming, an age-old male dominated musical profession. Informed by the theory of spatial trialectics, this article investigates gendered space in relation to dùndún drumming with a view to understanding the changing nuances of gender relations among the Yoruba of southwestern Nigeria. Ethnographic techniques were used to generate data on Àrà and Àyánbìnrin, two well-known urban popular female dùndún performers whose aspirations and career trajectories reside outside the Àyàn lineage and spiritual tradition. Biographical accounts and lived experiences of both artists suggest that women's agency in Yoruba drumming is hedged by different, prevailing socioeconomic contexts, including a determination to challenge limitations to a career path and economic progress. By describing how female dùndún drumming may be regarded as a response to social and musical change, and discussing how issues of masculinity and femininity are constructed, negotiated and contested, I argue that the belief forbidding women from playing Yoruba drums is not strictly applicable to the dùndún because the dùndún ensemble is more connected to social than religious performances.
Keywords: Gender; Gendered Space; Male Dominance; Yoruba Music; Drumming; Gender Issues; Female Drummers; African Music